Endogenous rhythm variation and adaptation to the tidal environment in the freshwater snail, Semisulcospira reiniana - Yokomizo, Takumi; Takahashi, Yuma (Frontiers in Ecology and Evolution, 2022)
Organisms have endogenous timekeeping system(s) to coordinate their biological processes with environmental cycles, allowing adaptation to external rhythmic changes in their environment. The change in endogenous rhythms could contribute to range expansion in a novel rhythmic environment. We hypothesized that populations of the freshwater snail near estuaries show a circatidal rhythm to synchronize with the tidal cycle. We compared the behavioral and gene expression rhythms between non-tidal and tidal populations of the freshwater snail, Semisulcospira reiniana. Individuals inhabiting tidal areas exhibited a rhythmic activity pattern coordinated with the tidal cycle under both field and laboratory conditions, but individuals inhabiting upstream non-tidal areas showed a circadian activity pattern. The proportion of circadian oscillating genes was greater in non-tidal than in tidal individuals, while that of circatidal oscillating genes was greater in tidal than in non-tidal individuals. Additionally, transcriptome-wide population genetic analyses revealed that these two adjacent populations can be clearly distinguished genetically, though the genetic distance was very small. Our results provide evidence of the shift in an endogenous rhythm via range expansion to a novel rhythmic environment. The changes in a small number of genes and/or phenotypic plasticity may contribute to the difference in the endogenous rhythms between non-tidal and tidal populations.